Feasibility and efficacy of intraoperative neural monitoring in remote access robotic and endoscopic thyroidectomy. (April 2020) - Ji, Yong Bae; Ko, Seok Hwa; Song, Chang Myeon; Sung, Eui Suk; Lee, Byung-Joo; Wu, Che-Wei; Chiang, Feng-Yu; Tae, Kyung
Highlights: We evaluated the efficacy of IONM in remote access thyroidectomy. The success rate of IONM was lower compared to conventional thyroidectomy. Obtaining the vagus nerve EMG signal was relatively difficult. It was difficult to follow the troubleshooting algorithm. IONM helps confirm the RLN and predict nerve function. Abstract: Objectives: We performed this study to assess the feasibility and efficacy of intraoperative neural monitoring (IONM) in remote access robotic and endoscopic thyroidectomy. Materials and methods: We studied 104 consecutive patients (122 nerves at risk, NARs) who underwent robotic or endoscopic thyroidectomy via a postauricular facelift approach or transoral approach while performing intermittent IONM. Results: IONM was successful in 86/104 patients (82.7%). The success rate was significantly lower in the first 15 cases using a transoral approach than in the subsequent cases (7/15 vs. 41/43, p < 0.001). The standard IONM procedure (obtaining V1/R1/R2/V2 signals) was performed on 32/42 NARs (76.2%) undergoing thyroidectomy via a facelift approach and 10/58 NARs (17.2%) undergoing thyroidectomy via a transoral approach (p < 0.001). Loss of signal occurred in 6/100 NARs in 86 patients receiving successful IONM. Of these 6 LOS, 5 were false positives, and 1 was a true positive. A false negative occurred in 1/100 NARs. The sensitivity, specificity, positive and negative predictive values of IONM were 50.0%, 94.9% 16.7% and 98.9%, respectively. Conclusions: The failure rate of IONM in remote access thyroidectomy is relatively high and following the standard IONM procedure is also relatively difficult. However, IONM is more helpful in confirming the recurrent laryngeal nerve (RLN) and predicting that it is functional in the limited working space available than it is in conventional thyroid surgery.